2015
DOI: 10.1016/j.invent.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Online prevention of postpartum depression for Spanish- and English-speaking pregnant women: A pilot randomized controlled trial

Abstract: Background Postpartum depression (PPD) is a maternal mental health problem that affects women from all regions of the world. Unfortunately, even in developed countries, half of the cases go undetected and, consequently, untreated. Individuals from low and middle income countries trend toward underutilization of mental health services, partly due to the limited number of available psychological resources. The primary aims of this pilot randomized controlled trial were to adapt to the Internet the Mothers and Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(146 citation statements)
references
References 57 publications
2
139
0
Order By: Relevance
“…Individuals who successfully completed the online programmes frequently experienced benefits including reduction in symptoms of depression and anxiety and improved quality of life. One study 54 aimed at prevention of post-partum depression recruited Spanish-speaking participants from 23 countries, mostly in Latin America. This study showed that online self-help programmes can promote mental wellbeing among individuals residing in both high-income and lower income countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who successfully completed the online programmes frequently experienced benefits including reduction in symptoms of depression and anxiety and improved quality of life. One study 54 aimed at prevention of post-partum depression recruited Spanish-speaking participants from 23 countries, mostly in Latin America. This study showed that online self-help programmes can promote mental wellbeing among individuals residing in both high-income and lower income countries.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that online self-help programmes can promote mental wellbeing among individuals residing in both high-income and lower income countries. 54 …”
Section: Resultsmentioning
confidence: 99%
“…Research supporting the utility of Internet interventions for PPD prevention and treatment is more limited. Several trials have demonstrated preliminary effectiveness for prevention of PPD (e.g., Barrera, Wickham, & Muñoz, 2015;Haga, Drozd, Brendryen, & Slinning, 2013;Jones et al, 2013) as well as treatment (e.g., Danaher et al, 2012;O'Mahen et al, 2014;O'Mahen et al, 2013). However, additional trials are necessary to better understand both the utility and limitations of Internet interventions for women in the perinatal period who either have or may be at risk of developing PPD.…”
Section: Introductionmentioning
confidence: 99%
“…Data for this report were extracted from the baseline assessment of a larger trial that examined the efficacy of an online prevention of postpartum depression (PPD) intervention (see Barrera, Wickham, & Muñoz, 2015). Participants were recruited online using sponsored links (see Barrera, Kelman, & Muñoz, 2014) and were directed to the online consent form if they were female, pregnant (at any stage), and over 18 years of age.…”
Section: Methodsmentioning
confidence: 99%